2017
DOI: 10.1021/acs.jpclett.7b01005
|View full text |Cite|
|
Sign up to set email alerts
|

pH-Dependent Inversion of Hofmeister Trends in the Water Structure of the Electrical Double Layer

Abstract: Specific ion effects (SIEs) are known to influence the acid/base behavior of silica and the interfacial structure of water, yet evidence of the effect of pH on SIEs is lacking. Here broadband vibrational sum frequency generation (SFG) spectroscopy was used to study SIEs on the water structure at the electrical double layer (EDL) of silica as a function of pH and monovalent cation identity from pH 2-12 at 0.5 M salt concentration. SFG results indicate a direct Hofmeister series of cation adsorption at pH 8 (Li … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
143
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(174 citation statements)
references
References 64 publications
20
143
3
6
Order By: Relevance
“…This provides additional evidence that the surfacesolution system significantly changes with the iteration of the TP. Regardless of the vague behavior of the confined liquid signal, optimizing this setup may ultimately allow us to extend our studies to investigate interfacial water melted between ice and solid surface or the so-called quasi-liquid layer (Nagata et al, 2019;Li and Somorjai, 2007;Rosenberg, 2005;Döppenschmidt et al, 1998), which also has industrial applications (e.g., ski sports or frozen-food packaging).…”
Section: Confined Liquid and Ice Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides additional evidence that the surfacesolution system significantly changes with the iteration of the TP. Regardless of the vague behavior of the confined liquid signal, optimizing this setup may ultimately allow us to extend our studies to investigate interfacial water melted between ice and solid surface or the so-called quasi-liquid layer (Nagata et al, 2019;Li and Somorjai, 2007;Rosenberg, 2005;Döppenschmidt et al, 1998), which also has industrial applications (e.g., ski sports or frozen-food packaging).…”
Section: Confined Liquid and Ice Signalmentioning
confidence: 99%
“…In principle it may be present in the form of crystalline or amorphous SiO 2 -or Si-containing minerals. Both crystalline and amorphous forms of SiO 2 have been widely studied (Iler, 1979;Bergna and Roberts, 2005) and have also been studied with interfacial behavior including the silicawater interface under static conditions using nonlinear spectroscopy techniques (Ong et al, 1992;Ostroverkhov et al, 2004Ostroverkhov et al, , 2005Jena and Hore, 2009;Jena et al, 2011;Azam et al, 2012Azam et al, , 2013Dalstein et al, 2017;Darlington et al, 2017;DeWalt-Kerian et al, 2017;Schaefer et al, 2017Schaefer et al, , 2018Boamah et al, 2018), potentiometric titration (Karlsson et al, 2001;Dove and Craven, 2005), atomic force microscopy (Morag et al, 2013), or X-ray photoelectron spectroscopy (Brown et al, 2016). However, studies under non-equilibrium conditions are rare (Gibbs-Davis et al, 2008;Lis et al, 2014;Schaefer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this broad applicability, the Hofmeister series and similar empirical trends in SIE have been extensively studied to understand the effects of ions that cannot be simply explained by their charge and ionic concentration. [3][4][5][14][15][16][17] The majority of these studies use the concept of "series" to explain certain physicochemical effects of ions being "more" or "less" for one ion compared to another one.Although useful in many cases, this language inevitably implies a possible single underlying mechanism to explain SIE. However, with the advancement of molecular-scale probes that can directly observe SIE at interfaces, it has become evident that such simple and universal explanation, possibly, does not exist.…”
mentioning
confidence: 99%
“…[42][43][44]117 Despite these challenges, recent years have seen some significant progress: For instance, ion identity (element and charge), electrolyte concentration, and bulk solution pH are some of the factors that are now known to control surface charge density and the structure of interfacial water molecules and the hydrogen-bond networks they establish within the electrical double layer. [12][13][14][15][16][17] Moreover, potentiometric measurements and calculations with surface complexation models have established that cations and anions influence charge densities at silica/water interfaces via their adsorption affinities. [18][19][20] Likewise, nonlinear optical measurements have revealed that halide and alkali ions influence silanol group dissociation at silica/water interfaces, [21][22][23] a result that perhaps is linked to reports that certain alkali chlorides at high ionic strengths enhance silica dissolution rates.…”
mentioning
confidence: 99%